EXPRESSION OF IMUNOGLOBULIN, GRANZYME-B AND PERFORIN AGAINTS Ag85A AND Ag85B PROTEINS OF MYCOBACTERIUM TUBERCULOSIS IN BALB/C MICE - Fihiruddin, Fihiruddin; Artama, Wayan Tunas; Wibawa, Tri; Mertaniasih, Ni Made (African Journal of Infectious Diseases (AJID), 2019)
Background: Ag85 is a protein that may maintain survival of M.tuberculosis in intracellular parts of host cells and is considered as a virulence factor. The expression of Ag85 protein can stimulate proliferation and differentiation of B cells and T cells in patients with tuberculosis. This research aimed to determine the ability of Ag85A and Ag85B proteins in activating the response of antibodies, granzyme-B and perforin in Balb/c mice.Methods: 25 male Balb/c mice were assigned into five groups. Group I was treated with adjuvant, group II with BCG vaccine (Biofarma), group III with a combination of BCG and Ag85A, group IV with a combination of BCG and Ag85B and group V with a combination of BCG, Ag85A and Ag85B. Concentrations of Immunoglobulin G, granzym-B and perforin were examined using ELISA and the number of CD8+ T-cells and NK T-cells were checked by flowcytometry.Results: The highest concentration of imunoglobulin G was found in group-V with 62.49±5.4327 ng/ml. The highest mean number of CD8+ T-cells, NK T-cells, granzyme-B and perforin was found in group–IV with 4.32%, 1.03%, 35.11±1.7789 pg/ml and 6.19±0.2235 pg/ml respectively. The results of One-Way Anova test showed that there were significant differences in immunoglobulin responses, with p <0.05. The expressions of granzym-B and perforin were higher in mice treated with combination of BCG and recombinant proteins.Conclusions: Ag85 protein can be combined with the BCG vaccine to improve protection against M. tuberculosis infection.